ACCOUNTABILITY ARISAN CULTURE BASED ON UKHUWAH ISLAMIYAH PERSPECTIVE - Leniwati, Driana; Khaqimah, Millatul; Agus Saputri, Novitasari (Universitas Airlangga, 2023)
The purpose of this research is to analyze accountability arisan culture based on Ukhuwah Islamiyah perspective. The research was conducted in Bangkalan, Madura. The method used is interpretivist paradigm with qualitative approach. Qualitative data obtained by conducting interviews. The informants in this research are the Arab social gathering community and religious expert. Data analysis techniques in this study are data reduction, data presentation, validity, and drawing conclusions. The research found the meaning of receivable in arisan in broader context than existing concept of receivable in accounting, namely arisan as ukhuwah Islamiyah, arisan as trust relationship, arisan as social spiritual responsibility and has become a culture in the arisan. Sincerity to help fellow members is an accountability not only to society but also to God. The obligation to pay the arisan which is intended not only because of an obligation but is also interpreted as a form of accountability to humans (social) and God which is manifested in the form of ukhuwah Islamiyah.